A Novel Homozygous TTC7A Missense Mutation Results in Familial Multiple Intestinal Atresia and Combined Immunodeficiency - Mou, Wenjun; Yang, Shen; Guo, Ruolan; Fu, Libing; Zhang, Li; Guo, Weihong; Du, Jingbin; He, Jianxin; Ren, Qinghua; Hao, Chanjuan; Gui, Jingang; Huang, Jinshi (Frontiers in Immunology, 2021)
Rare autosomal-recessive variants in tetratricopeptide repeat domain 7A (TTC7A) gene have been shown to cause intestinal and immune disorders of variable severity. Missense mutations in TTC7A gene, usually retaining most of the functional motifs, is associated with relative milder clinical presentations. In this study, we reported a patient suffered from severe multiple intestinal atresia (MIA) with combined immunodeficiency (CID) that led to the pyloric diaphragm, ileum atresia, and colon stenosis, and multiple episodes of sepsis. In spite of several surgeries and supportive treatment, the patient died of severe sepsis and multiple organ failure at age of 3 months. The whole exome sequencing (WES) of peripheral blood samples identified a novel homozygous TTC7A missense mutation (c. 206T>C, p. L69P) inherited from his parents with consanguineous marriage. In silico analysis revealed that a hydrogen bond present between Gly65 and Leu69 in the wild-type TTC7A was disrupted by the Leu69Pro mutation. Moreover, this homozygous missense mutation led to a reduced TTC7A expression in lymphocytes and intestinal tissues, accompanied by impeded lymphocyte development. Further studies demonstrated that the PI4K-FAM126A-EFR3A pathway was impaired in colon tissues. Our data strongly support the linkage of severe MIA-CID with the missense mutation in TTC7A gene. More knowledge of the TTC7A protein functions will have important therapeutic implications for patients with MIA-CID.